State Aid for Development of Manufacture of Agricultural Machinery: Economic and Statistical Aspect - Krekhivskyi, O. V. (Statistics of Ukraine, 2022)
The world practice of state support of agricultural machinery is studied. Features of dualistic agro-industrial policy of China are identified. It is substantiated that the subsidy policy for the purchase of agricultural machinery, which has been implemented by the Chinese government since 2004, has also had an extensive impact on the promotion and development of agricultural mechanization, development of agricultural machinery and improvement of economic results, scaling up of services for agricultural sector; activation of related industries: the development of companies that specialize in construction and road equipment, the production of engineering products for agricultural sector. The evolution of state support is shown: changes in the priorities of industry development and the number of subsidies for the purchase of equipment, the development of which is encouraged. It is established that the support of decision-making on the implementation of state support is provided by scientific institutions, relevant associations, information and analytical agencies. It is shown that the generated statistical databases allow to analyze the scale and structure of sales of machinery to farmers with state subsidies (by categories, manufacturers, regions), calculate China’s agricultural machinery market sentiment index (AMI), among the components of which - Agricultural Machinery Subsidy Index. It is stated that on the initiative of the National Committee for Industrial Development a mechanism of partial compensation of the cost of machinery and equipment for agro-industrial complex, which has a certain level of localization of production in Ukraine, was launched in Ukraine in 2017. Summing up the results of the implementation of this mechanism for the national economy are presented. The necessity of expanding state support is substantiated: introduction of incentives for technological innovations of enterprises and partial compensation of interest on loans for the purchase of Ukrainian made agricultural machinery. Following the example of China, it is proposed to improve the mechanism of partial compensation by adjusting the upper limit of aid intensity in accordance with the cost of machinery and equipment for farmers and its innovation. It is substantiated that the lack of multifaceted monitoring of the implementation of the partial compensation mechanism makes it impossible to assess its consequences for machine builders, farmers and the economy as a whole (primarily in terms of the effects obtained). The introduction of statistical and information-analytical support for the implementation of the state aid mechanism in Ukraine will facilitate both timely control and management decisions-making on future support by the state, and the strategic business planning of farmers and machine builders.